Smart dustbin / Nurfarahin Mohamed & Zafirah Zainuddin - Mohamed, Nurfarahin; Zainuddin, Zafirah (2015)
Microcontroller is the device is powerful device. Nowadays, the good things are the powerful component, microcontroller is one of the component best components and it is basically very simple. Microcontroller is the brain of any electronic devices. It is a simplest computer processor main brain for the future system. It has many type of microcontroller from the lowest to the higher number of pins with so many functions at the pins. It is need simple software to control it all and everyone can easily learn about has been developed. The microcontroller has a large number of different types and software but it has many common similarities. When the power supply is turned off the program is loaded into the microcontroller. When the power supply is on everything is start at the high speed. The control unit is take part to keep under control. Then it disables all other circuit except the quartz oscillator. Power supply reaches the maximum and oscillator frequency become stable and all the pins are configured as the inputs. The overall electronics start operation in rhythm with pulse sequence. Microcontroller is compatible with any assembly language. The special feature of the microcontroller is it has Read Only Memory (ROM). ROM is the permanently memory and save permanently program being executed. Unlike the integrated circuits, microcontroller has been programmed first. This is why many of electronics engineer do not use microcontroller. But actually the programming for the microcontroller is very simple. In these recent years, the technologies are move faster than before. Many applications have been invented for making life easier by using microcontroller. Microcontroller can be applying in the robotics, toys and house appliances. Microcontroller is widely used for inventor. Nowadays, even the primary and secondary schools are study about the microcontroller. People that are able to use microcontroller make it as a hobby to make a programming. By using the microcontroller they able to make such an interesting project and does not require so much cost because microcontroller are cheap. Microcontroller are do it yourself project because it small and easy to carry and the software for the microcontroller is can be install in the personal computer.